الدلالة المجازية في روح المعاني استقصاء رأي الألوسي في ثبوت المجاز في النص القرآني - طبني, صفية (حوليات المخبر; No 02 (2014): مجلة حوليات المخبر)
للدلالة المجازية أهمية بالغة في تحديد معنى النص الذي وردت فيه و ذ لك عندما تتضافر مجموعة من القرائن المتصلة في ضبط تلك الدلالة فيتعدد المعنى حسب ما يقتضيه السياق ومنه فهم النص. والنص القرآني أجل النصوص؛فكانت الحاجة لفهمه وتدبر آياته من أجل الأعمال وقد أشار الألوسي في تفسيره روح المعاني لأهمية هذا المبحث في التأويل وبين أنه أبلغ وأقوى في بيان المعنى ليكون بذلك أحد المؤيدين لورود المجاز في القرآن الكريم بعكس الكثير من المفسرين . The metaphorical meaning has a significant importance  indicating the exact meaning of the text in which it occured. That happens when a set of  evidence is combined   to gevern that meaning and so the meaning  become diverse according to the context and.thus the meaning of the text. The Coranic text is the clearest one. The need to understand and contrive its verses has been of great importance. AhAlloussi mentioned in his book ' the spirit of meanings'  the importance of that research in the interpretation. He proved that it is strong and eloquent to convey meaning. For that reason he becomes one of  the supporters for the metaphor in the 'Coran' as opposed to many other interpreters.